Madrasas and recruitment of child soldiers: the scenario in Afghanistan - Eishan Jan, Mohammad Naqib (International Journal of Recent Technology and Engineering (IJRTE), 2019)
-This study focuses on the role of religious seminaries known as madrassas in Afghanistan in recruitment and use of child soldiers, since there is significant amount of credible research indicating the correlation between madrassas and child soldiering. The study also delves into the legal position of international and national legal regimes as well as Islamic legal standards on the issue of child soldiering. The research primarily relies on doctrinal method in sections where main sources of the national and international legislations are studied, and non-doctrinal, qualitative analysis of primary and secondary sources relevant to the topic. In addition to this, textual analysis of primary sources of Islamic law and legal rulings and justification for legal rulings by the authoritative figures of armed groups involved in recruitment of underage combatants for combat in Afghanistan is utilized. The research uses comparison between the international and national legal regimes on the one side and Islamic legal standards on the other side to ascertain similarities and differences. The study has found the three legal regimes under investigation have almost identical view pertaining to the lower age limit for the conscription of soldiers. As a result, the study has also established that many more underage students were recruited and used in hostilities in the armed conflict in Afghanistan during the last twenty years of the 20th century than it has been the case in the 21st century up to the present. Keywords: Madrasa; Recruitment of Child Soldier; Use of Child Soldier; Taliban; Islamic State in Khorasan; Shariah Law; Jihad; International law; Afghan law